Graphics programming in C : a comprehensive resource for every C programmer : covers CGA, EGA and VGA graphic displays and includes a complete toolbox of graphic routines and sample programs - 195170 Stevens, Roger T. (Redwood City, Calif. : M & T Books, 1988)
57